2009
DOI: 10.21273/hortsci.44.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulation of Bioprotectant Content of Red Leaf Lettuce with Light-emitting Diodes

Abstract: Lactuca sativa cv. Outredgeous was grown under either fluorescent lamps or light-emitting diodes (LEDs) to test the hypothesis that antioxidant potential could be regulated by light quality. Red leaf lettuce was grown at 300 μmol·m−2·s−1 of photosynthetically active radiation, 1200 μmol·mol−1 CO2, 23 °C, and an 18 h-light /6-h dark photoperiod in controlled-environment chambers. The LED treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
155
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 11 publications
15
155
1
7
Order By: Relevance
“…They reported that shoot DW increased with increasing red/blue light ratio, which was mainly due to increased leaf number and leaf area under the higher red/blue light ratio. It was also reported that the optimal red/blue light ratios for FW and DW accumulation were 7/3 in strawberry plantlet (Nhut et al, 2003) and 1/3 in rapeseed plantlets in vitro (Li et al, 2013), respectively, but 9 in cucumber seedlings (Hernández and Kubota, 2016), spinach (Yorio et al, 2001), lettuce (Bula et al, 1991; Yorio et al, 2001; Stutte et al, 2009), and Arabidopsis (Ooi et al, 2016). Based on the above discussion, blue light promote growth by stimulating morphological response.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that shoot DW increased with increasing red/blue light ratio, which was mainly due to increased leaf number and leaf area under the higher red/blue light ratio. It was also reported that the optimal red/blue light ratios for FW and DW accumulation were 7/3 in strawberry plantlet (Nhut et al, 2003) and 1/3 in rapeseed plantlets in vitro (Li et al, 2013), respectively, but 9 in cucumber seedlings (Hernández and Kubota, 2016), spinach (Yorio et al, 2001), lettuce (Bula et al, 1991; Yorio et al, 2001; Stutte et al, 2009), and Arabidopsis (Ooi et al, 2016). Based on the above discussion, blue light promote growth by stimulating morphological response.…”
Section: Discussionmentioning
confidence: 99%
“…The blue-type LED emits light with 460 nm λ p , which activates photosynthesis [22,29,30,32] and which induces phototropin-mediated and cryptochrome-mediated plant responses [33-38]. Blue light also enhances the accumulation of pigments such as chlorophylls in cucumber leaves [22], carotenoids in citrus juice sacs cultured in vitro [39], and anthocyanins in lettuce leaves [21]. Orange-red light with 630 nm λ p enhances photosynthesis [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…One of the main advantages of LEDs is the possibility of using specific light wavelengths for influencing plant morphology and phytochemical contents (Morrow, 2008;Tamulaitis et al, 2005). Data in the literature have mostly reported about successful cultivation of various plants under different lighting combinations of blue, red, and far-red LEDs (Kopsell & Sams, 2013;Olle & Viršilė , 2013;Stutte, Edney, & Skerritt, 2009;Tarakanov, Yakovleva, Konovalova, Paliutina, & Anisimov, 2012). However, there is insufficient information regarding effects of irradiance levels and other wavelengths in LED lighting systems, mostly designed to replace HPS lamps, which main spectral composition is in yellow-orange-red region (Morrow, 2008;Spaargaren, 2001) on plant metabolic composition, including carotenoids.…”
Section: Introductionmentioning
confidence: 99%